Metaphorical meaning in “Clothing” semantic field - Ghamoyan , Lusine (Bulletin of Yerevan University B: Philology, 2022)
The aim of the article is to study and identify the metaphorical meaning(s) of each word referring to the concept "clothes", which appears on the same word level, next to its main meaning, because the derivative meaning, which arises mainly from the figurative use of the word, is more stable. That is, every word, regardless of its set of meanings, having its primary meaning, can be used in conversation to denote objects, phenomena, features that are in some way related or similar to the object having a direct meaning, phenomenon, etc. During this period, the following semantic transitions occur: object → object, object → attribute, attribute → attribute, attribute → object. Metaphorical meaning is usually expressed by shape, color, size, similarity of other objects, nature of action, and other combinations. Changes in the meanings of words (especially figurative ones) of the semantic field "clothing" are also caused by wordformation factors. In word-formation suffixes, the components (word, root) retain their basic general meanings, and due to the complementary components of the base (bases), new meanings of the word are formed (including metaphorical ones) and new words are formed. The same noun in the semantic field of the word "clothing" at different stages of language development or in other variants of the literary language, as well as in dialects, can have completely different metaphorical meanings. The figurative meanings of words expressing the meaning of “clothing” also provide ample opportunities for the formation of many phraseological units.